SERIOUS LEISURE LEVEL AND WORK OF KOREAN WOMEN'S BASEBALL CLUBS - LEISURE CONFLICT - Kim, Mi-Lyang; Choi , Rak-Heung; Lee , Myeong-Ha (PEOPLE: International Journal of Social Sciences, 2024)
The purpose of this study is to verify the differences and relationships in work-leisure conflict based on the level of serious leisure among female baseball enthusiasts who participate in baseball as a serious leisure activity. To achieve this goal, a survey was conducted using a purposive sampling method among female baseball enthusiasts. Out of the collected surveys, a total of 175 were used for the final analysis, excluding 34 responses that were deemed insincere. In this study, exploratory factor analysis, cluster analysis, K-means cluster analysis, one-way analysis of variance (ANOVA), and multiple regression analysis methods were employed. The data collected were analyzed using SPSS 25.0 Program and AMOS 26.0 Program. The results of the analysis showed the following: Firstly, the analysis of differences in work-leisure conflict based on the level of serious leisure revealed a significant difference among female baseball enthusiasts. Secondly, the differences in the four sub-factors of work-leisure conflict based on the level of serious leisure were examined. Post-hoc analysis results indicated that only the negative affect_WL and time pressure_WL factors had significant differences based on the level of serious leisure. Thirdly, the impact of sub-factors of serious leisure on work-leisure conflict showed that only the personal effort factor had a negative influence on work-leisure conflict.This study aimed to elucidate the relationship between the level of serious leisure among female baseball enthusiasts participating in baseball as serious leisure and work-leisure conflict. Through this research, a deeper understanding of the lives of women participating in sports activities as serious leisure is sought